Socio-Economic Consequences of the Transition to Organic Agriculture and Its Impact on Ecotourism - KARABASSOV, Rassul; NURMAGANBETOV, Kairat; BODAUKHAN, Kairat; KULMAGANBETOVA, Aisulu; ORYNBEKOVA, Gulnar; OMARKHANOVA, Zhibek (Journal of Environmental Management and Tourism, 2023)
In recent decades, the growing interest of consumers in visiting relatively less commercialized natural areas has contributed to the growth of ecotourism. The impact of mass and uncontrolled ecotourism on natural resources has increased significantly. However, research in the field of ecotourism is fragmentary, creating gaps in the modern understanding of this topic. The author tries to restore the relationship between loyalty and ecological and careful recognition, attachment to places and healthy lifestyles that contribute to the development of ecotourism, because the integration of organic agrotourism and rural tourism, organic agriculture and non-toxic and healthy environment helps tourists to escape from the hustle and bustle of the city, enjoy rural life and meet the needs of healthy and a leisurely lifestyle. The aim of the study is to analyze the socio-economic consequences of the transition to organic agriculture in the Republic of Kazakhstan and its impact on ecotourism. With the growing interest and awareness of the ecological environment, ecotourism is becoming more and more popular, but it still creates problems for the sustainable development of the environment. To solve such problems, it is necessary to review the literature on ecotourism and identify important research topics and areas for future research.